Preparation and characterization of oil palm empty fruit bunch-derived adtivated carbon-grafted zif-8 for CO₂ capture - Quek Kye Shane (2017)
CO2 has been identified as one of the main contributors of global warming. Therefore, much effort has been put into looking for an alternative method for CO2 capture. In this study, activated carbon was prepared from Oil Palm Empty Fruit Bunch (EFB) via a 2-step physical activation process with CO2 as the activation gas. Different parameters for the preparation of activated carbon were investigated for their yield and CO2 capture capabilities. The yield of activated carbon obtained ranged from between 20 - 26%, whereas the CO2 uptake capacity ranged from between 1850 - 2090 μmol/g. Of the three parameters investigated, activation temperature plays the most significant role, whereby higher activation temperature decreases yield and CO2 uptake. It was determined that the optimum temperature for the preparation of activated carbon is 500 °C with a dwell time of 1 hour. By using these conditions, a yield of 25.57% is obtained and a surface area of 548.1 m2 g-1 is achieved. This activated carbon with the most promising results was then grafted with ZIF-8 to further enhance its CO2 uptake capacity. Zeolitic Imidazolate Frameworks (ZIFs) are porous crystals with extended 3D structures, that has been widely studied for both water based applications, as well as various gas capture. ZIF-8 was chosen in this study to be grafted onto the activated carbon based on previous literature which shows promising CO2 capture capabilities and also its high surface area. The grafting method used in this study was the soaking method with capillary action. Activated carbon was soaked in ZIF-8 precursors (Zn(NO3)2•6H2O) and the ZIF-8 was synthesized in-situ. When the activated carbon was grafted with ZIF-8, the surface area shows an increase from 548.1 m2 g-1 to 647.5 m2 g-1 , whereas the total pore volume also shows an increase from 0.2552 cm3 g to 0.3881 cm3 g. However, the CO2 uptake capacity shows only a small increased to 2100 μmol/g. As the AC-ZIF utilizes microporous adsorption, surface area and pore volume plays a significant role in CO2 uptake. While there is an increase in surface area and the pore volume, an increase CO2 uptake was not apparent. Surface morphology of the oil palm EFB, activated carbon and activated carbon grafted ZIF- 8 was carried out via SEM-EDX. Before activation, oil palm EFB showed under developed porous structure. Activated carbon however, showed much denser pores and ridges. After grafting with ZIF-8, the surface of the activated carbon has been completely covered with ZIF-8 crystals, proving that the grafting process is successful. BET analysis was carried out on the activated carbon prepared at SOO °C and 700 °C and also activated carbon grafted with ZIF-8. It shows that the activated carbon and AC-ZIF follows the microporous adsorption isotherm. ZIF-8 was successfully grafted onto activated carbon. The AC-ZIF follows microporous adsorption and has basic adsorption sites. However, the CO2 capture does not show significant improvements over the activated carbon prepared and more research should be carried out to reach the full potential of this adsorbent.